Classic Scrapie in Sheep with the ARR/ARR Prion Genotype in Germany and France - Groschup, Martin H. (Centers for Disease Control and Prevention, 2007)
In the past, natural scrapie and bovine spongiform encephalopathy (BSE) infections have essentially not been diagnosed in sheep homozygous for the A(136)R(154)R(171) haplotype of the prion protein. This genotype was therefore assumed to confer resistance to BSE and classic scrapie under natural exposure conditions. Hence, to exclude prions from the human food chain, massive breeding efforts have been undertaken in the European Union to amplify this gene. We report the identification of 2 natural scrapie cases in ARR/ARR sheep that have biochemical and transmission characteristics similar to cases of classic scrapie, although the abnormally folded prion protein (PrP(Sc)) was associated with a lower proteinase-K resistance. PrP(Sc) was clearly distinct from BSE prions passaged in sheep and from atypical scrapie prions. These findings strongly support the idea that scrapie prions are a mosaic of agents, which harbor different biologic properties, rather than a unique entity.